Unique mating behavior, and reproductive biology of a simultaneous hermaphroditic marine flatworm (Platyhelminthes, Tricladida, Maricola). Issue 1 (3rd March 2020) - Yang, Ying; Li, Jun‐Yu; Sluys, Ronald; Li, Wei‐Xuan; Li, Shuang‐Fei; Wang, An‐Tai
Abstract: Flatworms generally are simultaneous hermaphrodites that exhibit various kinds of mating behavior. Here we report on the mating behavior and reproductive biology of the planarian Paucumara falcata . We recognized three phases in its mating behavior: a courtship, copulation, and postcopulatory phase. During the last‐mentioned phase, the partners showed a unique and very characteristic behavior in which their bodies intertwined, forming a spiral. Histological study of partners in copula revealed that the sclerotic tip of the musculo‐parenchymatic organ pierces the body wall of the partner and then becomes lodged in its parenchyma, suggesting that this organ may act as an anchor, thus stabilizing the worms during copulation. Similar organs in other species of marine triclad may also perform a stabilizing role during copulation. During copulation in individuals of P. falcata, sperm transfer was reciprocal or only unilateral. Copulation duration ranged 13–35 min (average 20 ± 5 min), irrespective of whether the mating was successful (i.e., resulted in the production of fertile cocoons). The spiraling phase lasted on average 10 min; some worms did not show the postcopulatory spiraling phase during their mating behavior. After successful copulation, an individual worm produced 1–12 fertile cocoons over a period of 1–17 days; from a cocoon hatched either one young (in 70% of the cases), or two young worms.